Mapping complex profiles of light intensity with interferometric lithography. Issue 7 (9th March 2023) - Holmes, Joseph; Zhang, Mi; Greibe, Tine; Schaich, William L.; Jacobson, Stephen C.; Dragnea, Bogdan
Abstract : Complex light intensity patterns formed by closely-spaced multiple apertures in a metal film can be faithfully mapped with sub-wavelength resolution, from near-field to far-field, by interferometric lithography. Abstract : Solving Maxwell's equations numerically to map electromagnetic fields in the vicinity of nanostructured metal surfaces can be a daunting task when studying non-periodic, extended patterns. However, for many nanophotonic applications such as sensing or photovoltaics it is often important to have an accurate description of the actual, experimental spatial field distributions near device surfaces. In this article, we show that the complex light intensity patterns formed by closely-spaced multiple apertures in a metal film can be faithfully mapped with sub-wavelength resolution, from near-field to far-field, in the form of a 3D solid replica of isointensity surfaces. The permittivity of the metal film plays a role in shaping of the isointensity surfaces, over the entire examined spatial range, which is captured by simulations and confirmed experimentally.